Peningkatan Hasil Belajar Materi Keragaman Sosial Dan Budaya Indonesia Menggunakan Model Pembelajaran Kooperatif Tipe Sal Siswa Kelas VIIA Tahun Pelajaran 2022-2023 SMPN 12 Surabaya - Anna Aisyah Prihatin; Akhmad Qomaru Zaman (International Forum of Researchers and Lecturers, 2024)
Education is an effort to educate the nation's life so that they become fully human with the spirit of Pancasila. The learning process carried out by teachers tends to achieve curriculum material targets and emphasizes memorization rather than understanding. In terms of improving learning achievement, creative teachers are needed who make learning interesting and liked by students. SAL Type Cooperative Learning is a teaching method by distributing question and answer sheets with available alternative answers. The aim of this research is to improve learning outcomes for Indonesian Social and Cultural Diversity Material using SAL Type Cooperative Learning for Class VIIA students for the 2022-2023 academic year at SMPN 12 Surabaya. This research uses Classroom Action Research (PTK) with a descriptive qualitative and quantitative approach consisting of two cycles. The subjects of this research involved 30 students of class VII A. Qualitative data was collected through student activity observation sheets. Meanwhile, quantitative data was collected from learning outcomes tests. The results of the research showed that there was an increase in the learning outcomes of Class VII A students at SMPN 12 Surabaya, the average score for cycle 1 was 72.3, with the highest score being 90, there was 1 person, and the lowest score was 55, there were 4 people with learning completeness of 80.0% and the incomplete 20.0%. Meanwhile, the average score obtained for cycle II was 79.5 with the highest score being 100, there were 2 people, and the lowest score was 60, there were 2 people with 90.0% learning completeness and 10.0% incomplete.